PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, TOTAL ASSET TURNOVER TERHADAP PROFITABILITAS PERUSAHAAN SUB-SEKTOR KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2019 - Joshua Hutagaol; Romulo Sinabutar (Fakultas Ekonomi Universitas Advent Indonesia, 2020)
This purpose of this study to determine the effect of current ratio, debt to equity ratio and total asset turnover on profitability. Ten chemical sub-sector companies were used as samples in this study with a period of time of 3 years so the total sample used was as many as 30 samples. Variable testing of research is conducted with t (partial) and f (simultaneous) tests with a significance level (α) of 0.05 or 5%. Multiple linear regressions are used as a method for analyzing research data. This study found that current ratio has a negative and not significant effect on the profitability 0.158>0.05 with t count -1.455, debt to equity ratio has a negative and significant effect on profitability 0.017<0.05 with t count -2.540, and total asset turnover has a positive but not significant effect 0.161>0.05 with t count 1.444.